ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KEPATUHAN KONTROL PASIEN STROKE DI PUSKESMAS CIPTOMULYO MALANG - MUZIBURRAHMAN, 131411123027 (2016)
Compliance is one of the problems in patients with stroke. Poor compliance of treatment can lead to therapeutic failure that could reduce the quality of life of patients. This conditions can improve mortality and morbidity. This research aimed to determine factors that associated with compliance control of patients with stroke in Puskesmas Ciptomulyo Malang. The study design was crosssectional with samples of 30 respondents and obtained by total sampling. Data were collected with means of questionnaires. Analysis of the results using statistical test Chi-Square with α = 0.05, a significant association between compliance controls with knowledge (p = 0.028), the economic level (p = 0.000), motivation (p = 0.000), access health services ( p = 0.001), Family Support (p = 0.000). Based on result of analysis discrimant swowed that the factor most related is the economic level with a score of 0,820. Therefore, a good level of knowledge, a high economic level, the motivation was good, easy access health services, and a good family support will allow patients to control dutifully in the health center. Expected health center can maximize these factors as an initial step to improve the compliance control of patients with stroke.